2012
DOI: 10.1186/1746-1596-7-160
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic approach to interstitial pneumonias in a single centre: report on 88 cases

Abstract: BackgroundInterstitial pneumonias (IP) cover a broad spectrum of diseases. Open lung biopsies reveal histological patterns and suggest possible diagnoses. Complete clinical records are necessary for final diagnoses. Especially idiopathic interstitial pneumonias (IIP) according to the ATS/ERS classification can only be diagnosed under these predictions. The aim of this study was to compare the results of histological evaluations with the final diagnosis after interdisciplinary case evaluation.Patients and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…Surgical lung biopsy (SLB) is the gold standard for tissue sampling in ILD . Many subjects cannot be referred for an SLB because of the increased risk of perioperative morbidity and mortality brought about by a combination of advanced age, comorbidity and severe respiratory insufficiency or the presence of secondary pulmonary hypertension in advanced disease.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical lung biopsy (SLB) is the gold standard for tissue sampling in ILD . Many subjects cannot be referred for an SLB because of the increased risk of perioperative morbidity and mortality brought about by a combination of advanced age, comorbidity and severe respiratory insufficiency or the presence of secondary pulmonary hypertension in advanced disease.…”
Section: Introductionmentioning
confidence: 99%
“…Nach einer MDD wurde die Diagnose mit der einer SDD verglichen. In 3 Studien erfolgte die SDD durch einen Pneumologen [65,144,145], in einer durch einen Pneumologen oder Internisten [146] und in einer weiteren durch mehrere Pathologen [147]. In 3 Studien wurde die MDD-Diagnose durch einen Pneumologen, einen Radiologen und einen Pathologen [65,144,146], in einer durch einen Radiologen und einen Pathologen [65] und in einer weiteren durch einen Pneumologen und einen Pathologen [147] gestellt.…”
Section: Technik Der Transbronchialen Lungen-kryobiopsieunclassified
“…It is useful to diagnose as having BO clinically based on mosaic appearance on chest CT images or small airway obstructive impairment on pulmonary function test, but as confirmed diagnosis of BO requires lung specimens obtained by video-assisted thoracic surgery or autopsy, it may be difficult to make a correct antemortem diagnosis. Theegarten et al [4] reported that diagnosis of interstitial pneumonias, a group of quite rare diseases, by open lung biopsies required sufficient clinical information because of the overlap of histological patterns and especially in non idiopathic interstitial pneumonias, an interdisciplinary case evaluation was needed. Therefore, we believe it is necessary to find a correct diagnosis histologically.…”
Section: Discussionmentioning
confidence: 99%